Knowledge, attitude and practices of farmers on sustainable agriculture: a case study of ward 3, Chimanimani district, Zimbabwe - Chikukwa, Audience (BUSE, 2024)
Climate irregularities have become an ever-present phenomenon impacting the performance of agriculture in the world. Coupled with economic hardships in developing country particularly Sub-Saharan Africa, farmers are experiencing difficulties in withstanding climate related changes. This study was conducted to assess the knowledge, attitude and practices of farmers on sustainable agriculture among ward 3 dryland farmers in Chimanimani district. This study utilized the quantitative and qualitative methodology to unpack the subjective experiences of farmers with knowledge, attitude and practices on sustainable agriculture. The adoption of sustainable agriculture by farmers was studied using their knowledge, attitude and practices. The study found that the farming community of Chakohwa faces several climatic trends such as low rainfall, and extreme weather patterns. The study also highlighted the knowledge farmers have on sustainable agriculture such as water harvesting, hybrid seeds to withstand pressing climate trends in the area. The specific objectives of the study were: a) To measure knowledge of farmers on sustainable agriculture, b) To assess the attitude of farmers regarding sustainable. C) To investigate the sustainable practices farmers are doing in order to cope up with climate change. Agricultural production should be increased through sustainable solutions.
Keywords: Sustainable agriculture; climate change; farmer knowledge; farmer attitudes; farming practices; dryland farming; climate variability; adaptation strategies; water harvesting; hybrid seeds; smallholder farmers; Chimanimani District; Zimbabwe